2021
DOI: 10.3390/plants10030588
|View full text |Cite
|
Sign up to set email alerts
|

Phytogeographical Analysis and Ecological Factors of the Distribution of Orchidaceae Taxa in the Western Carpathians (Local study)

Abstract: In the years 2018–2020, we carried out large-scale mapping in the Western Carpathians with a focus on determining the biodiversity of taxa of the family Orchidaceae using field biogeographical research. We evaluated the research using phytogeographic analysis with an emphasis on selected ecological environmental factors (substrate: ecological land unit value, soil reaction (pH), terrain: slope (°), flow and hydrogeological productivity (m2.s−1) and average annual amounts of global radiation (kWh.m–2). A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…In this study, we explored the relationships between environmental factors and distribution patterns of Brachypetalum orchid species in southwest China. Moreover, we also found that many environmental factors played a significant role in the distribution of Brachypetalum orchid species in southwest China (Figure 9), which was consistent with the findings of previous studies [54].…”
Section: Relationships Between Environmental Factors and The Distribution Of Brachypetalum Orchids In Southwest Chinasupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we explored the relationships between environmental factors and distribution patterns of Brachypetalum orchid species in southwest China. Moreover, we also found that many environmental factors played a significant role in the distribution of Brachypetalum orchid species in southwest China (Figure 9), which was consistent with the findings of previous studies [54].…”
Section: Relationships Between Environmental Factors and The Distribution Of Brachypetalum Orchids In Southwest Chinasupporting
confidence: 92%
“…Therefore, it is sufficient to demonstrate that Brachypetalum orchids have strong habitat and ecological preferences for karst landform in southwest China. This is consistent with the findings of Wittlinger and Petrikovičová [54], who also agreed that the presence of orchids was concentrated primarily in a portion of the karst area.…”
Section: Distribution Patterns Of Brachypetalum Orchids In Southwest Chinasupporting
confidence: 91%
See 1 more Smart Citation
“…Currently, the limiting factors include climate change, which is gradually leading to a decline in biodiversity, which are also interconnected, and their solution is key to sustaining life on Earth. From this point of view, there is a need to place greater emphasis on the protection of nature, so that we can ensure optimal conditions for the preservation of the original European phytocenoses and zoocenoses [2,3]. The conversion of forests from complex natural ecosystems to simplified commercial woodlands is one of the major causes of biodiversity loss.…”
Section: Introductionmentioning
confidence: 99%